Uygur yazar Tursun Yunus'un tiyatro eserlerinin incelenmesi - Yımıer, Ayıxıangulı (My University, 2017)
Bu çalışmada, geçmişten bugüne kadar geçen zaman dilimi içerisinde Uygur Edebiyatı’nın gelişimi incelenmiştir. Bu kapsamda, Uygur Edebiyatı’nın karşılaştığı zorluklar ortaya konulmuştur. Öte yandan, Uygur Edebiyatı’nın yaşayan önemli isimlerinden olan Tursun Yunus’un hayatı incelenmiştir. Tursun Yunus’un 13 piyesinin incelenmesi de bu çalışmanın ana konusudur. Bu çerçevede, çalışmanın giriş bölümünde Klasik Uygur Edebiyatı’nın genel bir çerçevesi çizilerek, Çağdaş Uygur Edebiyatı’na geçiş incelenmiştir. Sonraki bölümde ise Tursun Yunus’un hayatı analiz edilmiş ve Uygur Edebiyatı’na katkısı ele alınmıştır. Son bölümde ise Tursun Yunus’un 13 piyesinin incelenmesi yapılmıştır.

In this study, the development of Uyghur literature has been examined in the period from the past to the present. In this context, the difficulties encountered by Uyghur literature have been revealed. On the other hand, the life of Tursun Yunus, one of the important living names of Uygur literature, has been examined. The thematic work of Tursun Yunus' 13 plays is also the main theme of this work. In this frame, in the introduction part of the study, a general framework of Classical Uyghur Literature was drawn and the transition to Contemporary Uyghur Literature was examined. At the next part, the life of Tursun Yunus was analyzed and his contribution to Uyghur Literature was discussed. In the last part, the detailed analysis of 13 plays of Tursun Yunus was done.
Keywords: piyesleri Uyghur literature; plays; Tiyatro; Tursun Yunus; Uyghur Theater; Uygur edebiyatı; Uygur Tiyatrosu